Evaluation of Biological Effects of Hydroalcoholic Extract of Hibiscus Rosa Sinensis Flowers on Alloxan Induced Diabetes in Rats - Pethe, Mohan; Yelwatkar, Samir; Manchalwar, Smita; Gujar, Vijay (Drug Research, 2017)
Aim and Objective The current study sought to investigate antidiabetic, hypolipidimic, antioxidant and histopathological effects of floral extract of Hibiscus rosa sinensis in Alloxan induced Diabetes in rats.Materials and Methods Study was conducted on 6 groups with 6 wistar rats in each group for the period of 4 weeks. Group I: served as normal control (NC), rats administered with gum acacia 1 ml daily, group II: consider as diabetic control (DC) treated with alloxon 150 mg/kg body wt. Whereas Hibiscus rosa-sinensis flower extract was given orally in group III (DE1), group IV (DE2), group V (DE3) at doses of 50, 100 and 200 mg/kg body weight dissolved in distilled water respectively. Group VI (DG) was given glibenclamide (5 mg/kg) as a standard drug and results were compared in reference to it.Results The results indicate that the test compound HEFHR (Hydroalcoholic extract of flower Hibiscus rosa-sinensis) has significant and sustained oral antidiabetic activity, comparable with the hypoglycemic effect of Glibenclamide and Sulphonylurea. Flower extract of HRS was more efficacious in lipid lowering effect and in antioxidative activity than glibenclamide. After 28 day treatment with flower extract, size of islets was significantly increased and necrosis and atrophy of islets were significantly improved; also increase in number and diameter of cell islets appeared to be regular as compared to the diabetic group.Conclusion HEFHR possesses significant antidiabetic, hypolipidemic and antioxidant properties as well as regeneration of beta cells in rats. Further evaluation of HEFHR is in progress.
Keywords: Alloxan induced diabetes; Hibiscus rosa sinensis; glibenclamide